Road Safety and First Aid Educational Program Among Alexandria Port Commercial Drivers - Elkaluby, Eman Ahmed; Mohamed, Ahlam Mahmoud; Mohammed, Neama Yousef (International Journal For Research In Health Sciences And Nursing, 2020)
Background: Road safety has recognized as a major public health concern. It has considered an important sustainable developmental issue as illustrated by its express inclusion in the 2030 Agenda for Sustainable Development Goals. Road crashes have been responsible for increasing number of deaths and disabilities worldwide with a disproportionate growth in developing countries. Egypt is one of top 10 countries in the world with highest mortality rates due to road crashes. In fact, these crashes related deaths and injuries are largely preventable, and its prevention can be achieved by raising the commercial drivers’ knowledge and skills in maintaining road safety in all conditions and environments. Aims: this study aims to assess the knowledge regarding road safety and first aid measures among the commercial drivers and measure the effect of implementing road safety and first aid educational program on commercial drivers’ knowledge regarding road safety practices and first aid in Alexandria - Egypt. Design: A quasi experimental study design was adopted to carry out this study. Setting: the study was conducted at Alexandria Sea Port including Alexandria and Dekhila Port. Subjects: forty drivers were selected using systematic random sample technique Tools: three tools were used; Tool (I) Personal Characteristics and Health Status of The Commercial Drivers Structured Interview Schedule, Tool (II) Commercial Drivers’ Knowledge Regarding Road Safety and First Aid Measures Assessment and Tool (III) Commercial Drivers’ Road Safety and First Aid Related Practices Assessment Checklist. Results: The findings of the present study revealed that commercial drivers had poor knowledge and practices regarding road safety and first aid measures moreover, the implementation of the educational program related to road safety and first aid leads to improvement in both total knowledge score and total practice score among the studied commercial drivers. Recommendations: As the commercial drivers are not formally taught a wide array of safe driving practices, the traffic unit should put legislation for obligatory first aid training and safe driving for every driver who looking for driving license issue. Because road safety is a shared responsibility the collaboration is needed between the Egyptian ambulance organization in the form of first aid training and providing special hot line for commercial cars in case of accidents.